Vulvar lesion is not always a Sexually Transmitted Infection: report of a case of vulvar hidradenoma papilliferum - Pacífico, Fernando Augusto (2024)
Vulvar hidradenoma papilliferum is a benign and rare cutaneous cancer of the apocrine sweat glands that commonly appears in the anogenital region of women of reproductive age between 25 and 40 years old. Its diagnosis may be difficult, sometimes being confused with Bartholin’s gland cysts, Fordyce’s angiokeratomas, and vulvar endometriosis, among other malignant vulvar lesions. Thus, the present study aimed to report the clinical picture, diagnosis, and treatment of a case of vulvar HP, highlighting the importance of differential diagnosis in vulvar lesions.